Pembangunan Jaringan Distribusi Air Bersih bagi Masyarakat Desa - Sonawan, Hery; Hermawan, M. Reza; Sofia, R. Evi; Rohadin, Rohadin; Prihastuty, Endang; Yudisworo, W. Djoko; Subiyanta, Erfan; Siswanto, Agus; Tohasan, Achmad; Wasiran, Wasiran; Heri, Junial (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
The community service activities in Kaduela Village, which were part of a matching fund program for the year 2023, were executed from July–December 2023 in accordance with the proposed activity plan. The objective of this initiative was to establish a comprehensive water pipeline infrastructure to provide clean water to the inhabitants of Bina Loka and Bina Bakti Hamlet, who lacked access to the numerous springs located in Kaduela Village. Proper and comprehensive piping planning was necessary to provide equitable distribution of water among community members in the two elevated hamlets relative to the water source. The process of addressing issues in Kaduela Village involved several sequential steps. These steps encompassed the collection of primary and secondary data, the depiction of the new piping network on a map of Kaduela Village, the simulation of the new piping network using Epanet software, the construction of the new piping network, and the subsequent commissioning of the system. The chosen pipe network configuration is a dead-end system, which was deemed appropriate for implementation in the Bina Loka and Bina Bakti hamlets, with the aim of providing water services to a total of 58 households in Bina Loka and 15 households in Bina Bakti. The process of pipeline network designing was conducted by Mechanical Engineering students from Universitas Pasundan and Universitas 17 Agustus 1945 Cirebon, under the supervision of their respective supervisors, utilizing the Epanet software. In addition to receiving funding under the 2023 matching fund program, this initiative also garnered comprehensive support from the BUMDES Arya Kamuning as the primary collaborator